Are vertical migrations driven by circadian behaviour? Decoupling of activity and depth use in a large riverine elasmobranch, the freshwater sawfish (Pristis pristis) - Adrian C. Gleiss; David L. Morgan; Jeff M. Whitty; James J. Keleher; Sabrina Fossette; Graeme C. Hays (Hydrobiologia, 2017)

A global assessment of freshwater fish introductions in mediterranean-climate regions - Sean M. Marr; Julian D. Olden; Fabien Leprieur; Ivan Arismendi; Marko Ćaleta; David L. Morgan; Annamaria Nocita; Radek Šanda; A. Serhan Tarkan; Emili García-Berthou (Hydrobiologia, 2013)

Description of the larval development of Galaxies maculatus in landlocked lentic and lotic systems in Western Australia - Andrew Chapman; David L. Morgan; Howard S. Gill (New Zealand Journal of Marine and Freshwater Research, 2009)
The larvae and larval development of Galaxias maculatus are described from a freshwater lake and a saline river in southwestern Western Australia. The size at hatching (7.0 mm total length) was similar to that recorded elsewhere for G. maculatus and the sequence of fin development (i.e., caudal, dorsal, anal, pectoral, and pelvic fins) was identical to that recorded for galaxiids generally. There were relative increases in the proportions of head length and body depth with larval growth and a decrease in proportion of pre‐anal length. Larvae from river habitats were smaller throughout larval stages of development than those from the lake. Fins of riverine fish began and completed development at a smaller size of fish than the lacustrine population, presumably as a response to the need for great motility at a smaller fish size in lotic environments.

Predation by rainbow trout (Oncorhynchus mykiss) on a Western Australian icon: Marron (Cherax cainii) - Michelle Y. Tay; Alan J. Lymbery; Stephen J. Beatty; David L. Morgan (New Zealand Journal of Marine and Freshwater Research, 2007)
Considerable numbers of rainbow trout (Oncorhynchus mykiss) are captively produced then stocked into many wild aquatic systems in Western Australia despite a lack of understanding of their impact on the highly endemic native fish and freshwater crayfish of the region. The diet of an introduced, yet self‐sustaining population of O. mykiss was examined at Churchman Brook Reservoir in the Canning River Catchment, Western Australia, between September and November 2004. The large endemic freshwater crayfish marron (Cherax cainii) , which supports an iconic recreational fishery in Western Australia, comprised 61% by volume of all O. mykiss stomachs examined. The contribution made by C. cainii to the assimilated biomass of O. mykiss was confirmed by stable isotope analyses, which revealed that it dominated the assimilated diet of larger O. mykiss . The substantial contribution of C. cainii to the diet of wild O. mykiss suggests that, at least in habitat limited water bodies, it is likely to have a considerable predatory impact on C. cainii populations and may compromise some elements of this iconic recreational fishery.

Distribution and impacts of introduced freshwater fishes in Western Australia - David L. Morgan; Howard S. Gill; Mark G. Maddern; Stephen J. Beatty (New Zealand Journal of Marine and Freshwater Research, 2004)
This paper presents comprehensive distributional data, from over 1300 sites, on introduced freshwater fishes in Western Australia. Currently, there are 10 species of introduced freshwater fish established in the inland waters of Western Australia. Most of the introduced fishes found here are those that have formed feral populations elsewhere in the world, and include members of the Salmonidae, i.e., rainbow trout (Oncorhynchus mykiss) and brown trout (Salmo trutta); Cyprinidae, i.e., goldfish (Carassius auratus) and carp (Cyprinus carpio); Poeciliidae, i.e., mosquitofish (Gambusia holbrooki) , one‐spot livebearer (Phalloceros caudi‐maculatus) , guppy (Poecilia reticulata) , and swordtail (Xiphophorus hellerii); Percidae, i.e., redfin perch (Perca fluviatilis) , and Cichlidae, i.e., Mozambique mouthbrooder or tilapia (Oreochromis mossambicus) . More recently, the eastern Australian silver perch (Bidyanus bidyanus) (Terapontidae), which was introduced for aquaculture, has been captured in the Swan River near Perth. It is not known whether this population is self‐maintaining. The majority of introduced species are confined to the south‐west, although four and one species have been recorded from the Pilbara and Kimberley, respectively. Some species are extremely common and widespread, e.g., G. holbrooki and P. fluviatilis , whereas others are far more restricted and may be confined to between one and three catchments, e.g., C. carpio, P. caudimaculatus, P. reticulata, X. hellerii, O. mossambicus , and B. bidyanus . The impact of these introduced fishes on native species varies, but ranges from predation, e.g., O. mykiss, S. trutta, G. holbrooki , and P. fluviatilis , to aggressiveness, e.g., G. holbrooki, X. hellerii , and O. mossambicus , and competition for food and habitat.